Copro-prevalence of Cryptosporidium in pigs of selected districtsin West coast of India: A preliminary study - H B, CHETHAN KUMAR; D S, CHANDISHA; RAJKUMAR, SOLOMON; N, SHIVASHARANAPPA; R, SUSITHA; S V, UDHARWAR; E B, CHAKURKAR (The Indian Journal of Animal Sciences, 2023)
In India, Cryptosporidium spp. have been detected and characterised from humans and domestic animals, mostly ruminants. Although pigs can act as an important reservoir of Cryptosporidium infection to humans, comprehensive studies have not been conducted in pig population in India. Hence, present study attempt to elucidate the prevalence and diversity of Cryptosporidium infection in pigs in the selected districts of three states situated in the West coast of India. The pig faecal samples (n=221) were subjected to coprological examination using modified Ziehl Neelsen (mZN) staining method, followed by polymerase chain reaction to detect Cryptosporidium spp. Using mZN staining method, 1.35% (95% CI, 0.46%–3.91%) of the samples were found positive for Cryptosporidium oocyst. However, the DNA from Cryptosporidium positive faecal samples could not be amplified using polymerase chain reaction probably because of the low sensitivity of the PCR and or low oocyst number in the faecal sample. Cryptosporidium spp. of pig origin have zoonotic potential and a certain proportion of pigs infected with Cryptosporidium may be apparently healthy. Therefore, the pig farmers need to be made aware of hygienic practices while handling pigs and pig manure and and general public must be made sensitised about the good agricultural practices and standard food hygiene practices to prevent foodborne Cryptosporidium infection.